2023
DOI: 10.1039/d2ay01646j
|View full text |Cite
|
Sign up to set email alerts
|

Development of a designed comparison method based on isotope dilution liquid chromatography–tandem mass spectrometry for determining plasma renin activity and its clinical assessment of renin activity stability in plasma

Abstract: This study explored the optimized plasma incubation strategies and a traceable, robust, and reproducible designed comparison method based on LC-MS/MS for quantifying plasma renin activity, which is expected to harmonize laboratory measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[1][2][3] Liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) is one of the most powerful analytical techniques for quantitative bioanalysis. [4][5][6] Study of LC-MS/MS analysis for quantication of nucleobases, nucleosides, and nucleotides has been widely reported, 7,8 and reviews on this subject can be found in the literature. 9,10 In an LC-MS/MS analysis of biological uids such as urine, a sample pretreatment by solid-phase extraction (SPE) is normally carried out to isolate the analytes from the complex sample matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) is one of the most powerful analytical techniques for quantitative bioanalysis. [4][5][6] Study of LC-MS/MS analysis for quantication of nucleobases, nucleosides, and nucleotides has been widely reported, 7,8 and reviews on this subject can be found in the literature. 9,10 In an LC-MS/MS analysis of biological uids such as urine, a sample pretreatment by solid-phase extraction (SPE) is normally carried out to isolate the analytes from the complex sample matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It involves the conversion of these compounds to their respective ethenoderivatives with chloroacetaldehyde (CAA). CAA is known to react with nucleobases, forming etheno-derivatives: 1,N 6 etheno-adenine (3-A), 3,N 4 -etheno-cytosine (3-C), N 2,3 -etheno-guanine (N2,3-3-G), and 1,N 2 -etheno-guanine (1,N 2 -3-G). 1,27 It's expected that the increased structural aromaticity in ethenoderivatives overcomes the difficulties associated with the high hydrophilicity of intact nucleobases and nucleosides in the LC-MS analysis.…”
Section: Introductionmentioning
confidence: 99%